Sectoral differences in determinants of export intensity. Issue 2 (3rd March 2016) - Mac An Bhaird, Ciarán; Curran, Declan
Abstract: This study investigates firm characteristic determinants of export intensity in small firms. The originality of our approach is a comparative analysis of export intensity between firms in the computer software and manufacturing sectors, using a quasi-maximum likelihood estimation to test for the correct specification of the conditional mean model. Results indicate that larger, younger firms have greater export intensity in the computer software sector than in manufacturing. Research and development expenditure is equally important for export intensity in both sectors, but patent income is not significant. Sourcing managerial advice and expertise from the national development agency is important for firms in the manufacturing industry, but not for computer software firms. It is therefore important for export promotion organisations to publicise supports, as few small firms are aware of their availability. Our findings are especially valuable for policy makers concerned with low levels of export intensity among small firms.